The fusion of horizons: The possibility of a genuine ethical dialogue - YILMAZ, ERDAL (My University, 2022)
This article seeks the possibility of a genuine ethical dialogue based on Gadamer’s notion of a \"fusion of horizons\". For Gadamer, the human being is blessed with the unique ability to understand, and understanding is modelled on the act of conversation in which we engage with others. The fact that different points of view of dialogue partners merge in the process of understanding leads them to a better and mutual understanding, which is a fusion of horizons. For some of Gadamer’s critics, in the fusion, the more dominant horizon assimilates the other, which is why Gadamer’s notion of understanding seems to be unethical. To avoid this misinterpretation of the process of understanding, I will interpret Gadamer’s notion of understanding as the fusion of horizons based on his analysis of the concepts of \"dialogue\" and \"play\" (Spiel). By doing that, I aim at showing that Gadamer’s notion of the fusion of horizons is a dynamic process and that the latter requires an \"openness\" of participants to each other, which leads their encounter toward a genuine ethical dialogue.
Keywords: Sosyal ve Beşeri Bilimler; Felsefe; Sistematik Felsefe ve Mantık; Social Sciences and Humanities; Philosophy; Systematic Philosopy and Logic; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; FELSEFE; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; PHILOSOPHY; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities